Targeting Glutamine Metabolism Ameliorates Autoimmune Hepatitis via Inhibiting T Cell Activation and Differentiation - Yu, Qiang; Tu, Honghu; Yin, Xueyi; Peng, Chang; Dou, Chuanyun; Yang, Wenhua; Wu, Wenbiao; Guan, Xiaotong; Li, Jia; Yan, Hexin; Zang, Yi; Jiang, Haowen; et al. (Frontiers in Immunology, 2022)
Background: Autoimmune hepatitis (AIH) is mediated by a cascade of T cell-mediated events directed at liver cells and persistent inflammation within the liver can eventually result in liver cirrhosis. Targeting glutamine metabolism has an impact on T cell activation and differentiation. However, the effect of glutamine metabolism blocking upon AIH remains unknown. We use glutaminase antagonist 6-diazo-5-oxo-L-norleucine (DON) for in vitro assays and its prodrug 2-(2-amino-4-methylpentanamido)-DON (JHU083) for in vivo assays to investigate the potential therapeutic effect and molecular mechanism of glutamine metabolism blocking in an AIH murine model. Methods: AIH mice were treated with JHU083 or vehicle before concanavalin A (ConA) administration, and disease severity was examined. Then activation and differentiation (including Th1/Th17 cells and cytotoxic T lymphocytes (CTL)) of T cells from Vehicle-WT, JHU083-AIH and Vehicle-AIH mice were tested. Furthermore, in vitro T cell activation and differentiation were measured using separated splenocytes stimulated with ConA with or without DON. The activation and differentiation of T cells were tested using flow cytometry, qRT-PCR and ELISA. Phosphorylation level of mammalian target of rapamycin (mTOR) and 70 kDa ribosomal protein S6 kinase (P70S6K) were examined by western blotting. Results: JHU083 and DON significantly suppressed the activation of T cells and inhibited the differentiation of Th1/Th17 cells and CTL in vivo and in vitro. Besides, we demonstrated that glutamine metabolism blocking inhibited T cells activation and differentiation through decreasing the mRNA expression of amino acid transporter solute carrier family 7 member 5 (SLC7A5) and mitigating the activation of mTOR signaling. Conclusions: We proved that targeting glutamine metabolism represents a potential new treatment strategy for patients with AIH and other T cell-mediated disease. Mechanistically, we demonstrated that glutamine metabolism blocking inhibits T cells activation and suppresses the differentiation of Th1/Th17 cells and CTL.